2013
DOI: 10.1542/hpeds.2012-0071
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Management of Preterm Infants With Bronchiolitis

Abstract: OBJECTIVES:The goal of this study was to determine physician management choices for hospitalized premature infants with bronchiolitis compared with term infants and to evaluate predictors of steroid use in premature infants. METHODS:A chart review was conducted of premature and nonpremature infants admitted to 2 children's hospitals with bronchiolitis. Reviewers selected charts based on International Classifi cation of Diseases, Ninth Revision diagnosis codes and collected demographic and historical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Premature infants are at increased risk of asthma, which typically responds well to corticosteroids as these children get older. However, a retrospective study of premature infants under 2 years of age with bronchiolitis demonstrated no association between corticosteroid use and length of stay, even in the subset of premature infants responding to albuterol …”
Section: Resultsmentioning
confidence: 99%
“…Premature infants are at increased risk of asthma, which typically responds well to corticosteroids as these children get older. However, a retrospective study of premature infants under 2 years of age with bronchiolitis demonstrated no association between corticosteroid use and length of stay, even in the subset of premature infants responding to albuterol …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen percent of premature infants develop bronchiolitis and have longer hospital stays and more severe disease associated with that bronchiolitis compared to term infants [16, 1821] In premature infants less than 29 weeks GA, almost half of the infants will be admitted to the hospital for respiratory distress at some point [22]. Moreover, the rate of severe ARI is high in infants who live in developing countries, with up to 25% having severe ARI during the first year of life [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmada üçüncü basamak bir hastanenin çocuk acil servisinde kan gazı analizi yapılmış olan hastaların dosyaları retrospektif değerlendirilerek, kan gazı analizi ile hastaların ICD kodları arasındaki ilişki değerlendirildi. (8)(9)(10)(11)(12)(13)(14)(15). KGA'nin, ağır tavma geçiren ve majör damar yaralanması olan hastalarda olayın ciddiyetini gösterdiğini bildiren yayınlar literatürde yer almaktadır (16,17).…”
unclassified